Wakaf: Conflict of jurisdiction between civil and syariah courts in Malaysia - Md Dahlan, Nuarrual Hilal; Megat Latif, Hairuddin (Muna Management Services & Enterprise, 2003)
The jurisdiction of the syariah courts to hear matters involving wakaf is provided in List II to the 9th Schedule of the FC and the provisions in the respective states' enactments on the administration of Islamic affair enactments (hereinafter referred to as 'the said provisions'). Alas, this has otherwise been decided and negated by the civil court. Based on the decided cases, even though the jurisdiction to hear wakaf exclusively is under the jurisdiction of the syariah court, yet the civil court vehemently decided otherwise, viz it is under their domain. This clearly negates the importance of article 121(1A) of the FC. This paper intends to study the decided cases involving wakaf since the inclusion of sub clause 1A to article 121 of the FC, which has bestowed upon the syariah courts, exclusive and unfettered jurisdiction and power to adjudicate and determine their own matters as provided in the said provisions and to identify the real legal and jurisprudential issues, causes and stumbling blocks which have hitherto barred the syariah courts from having the freedom and ability to decide on wakaf and further to give suggestion and solution in the problem of conflict of jurisdiction of between these courts, civil and syariah, in matters pertaining to the same. It is hoped that through the illumination of this paper on wakaf and its conflict of jurisdiction between both courts in Malaysia, will give us some insights as to how issues on wakaf and its disputes were and are currently determined.